Roles of estrogens, estrogen-like compounds, and endocrine disruptors in adipocytes - Lizcano, Fernando (Frontiers in Endocrinology, 2022)
Women are subject to constitutional changes after menopause, which increases conditions and diseases prone to cardiovascular risks such as obesity and diabetes mellitus. Both estrogens and androgens influence the individual’s metabolic mechanism, which controls the fat distribution and the hypothalamic organization of the regulatory centers of hunger and satiety. While androgens tend to accumulate fat in the splanchnic and the visceral region with an increase in cardiovascular risk, estrogens generate more subcutaneous and extremity distribution of adipose tissue. The absence of estrogen during menopause seems to be the main factor that gives rise to the greater predisposition of women to suffer cardiovascular alterations. However, the mechanisms by which estrogens regulate the energy condition of people are not recognized. Estrogens have several mechanisms of action, which mainly include the modification of specific receptors that belong to the steroid receptor superfamily. The alpha estrogen receptors (ERα) and the beta receptors (ERβ) have a fundamental role in the metabolic control of the individual, with a very characteristic corporal distribution that exerts an influence on the metabolism of lipids and glucose. Despite the significant amount of knowledge in this field, many of the regulatory mechanisms exerted by estrogens and ER continue to be clarified. This review will discuss the role of estrogens and their receptors on the central regulation of caloric expenditure and the influence they exert on the differentiation and function of adipocytes. Furthermore, chemical substances with a hormonal activity that cause endocrine disruption with affectation on estrogen receptors will be considered. Finally, the different medical therapies for the vasomotor manifestations of menopause and their role in reducing obesity, diabetes, and cardiovascular risk will be analyzed.